2021
DOI: 10.1108/jedt-09-2021-0477
|View full text |Cite
|
Sign up to set email alerts
|

Durability and microstructure study of alkali-activated slag concrete with quartz sand subjected to different exposure conditions

Abstract: Purpose One of the sources for the increase in the carbon footprint on the earth is the manufacturing of cement, which causes a severer environmental impact. Abundant research is going on to diminish CO2 content in the atmosphere by appropriate utilization of waste by-products of industries. Alkali-activated slag concrete (AASC) is an innovative green new concrete made by complete replacement of cement various supplementary cementitious raw materials. Concrete is a versatile material used in different fields o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…research showed that a NaOH treatment greatly improves the mechanical properties of crete, prompted by the high territory. This occurs because NaOH accelerates the decom tion of the high territory so that it reforms into Na2SiO3 and NaAlO2 [28][29][30], and reaction with the Ca(OH)2 produced by the hydration of the cement causes the formati hydrated silicate and hydrated silica-aluminate gels, which makes AAZC-4 similar to OC gels fill the pore structures of the eco-friendly concrete, improving its compactness strength [31]. Due to the lower addition of NaOH in AAZC-2, the ZP and ASP particles decom insufficiently; thus, the effect of the volcanic ash on the composite cement materia improved but was lower than that of AAZC-4.…”
Section: Compressive Strength and Tensile Splitting-strength Experimentsmentioning
confidence: 99%
“…research showed that a NaOH treatment greatly improves the mechanical properties of crete, prompted by the high territory. This occurs because NaOH accelerates the decom tion of the high territory so that it reforms into Na2SiO3 and NaAlO2 [28][29][30], and reaction with the Ca(OH)2 produced by the hydration of the cement causes the formati hydrated silicate and hydrated silica-aluminate gels, which makes AAZC-4 similar to OC gels fill the pore structures of the eco-friendly concrete, improving its compactness strength [31]. Due to the lower addition of NaOH in AAZC-2, the ZP and ASP particles decom insufficiently; thus, the effect of the volcanic ash on the composite cement materia improved but was lower than that of AAZC-4.…”
Section: Compressive Strength and Tensile Splitting-strength Experimentsmentioning
confidence: 99%